EVALUATION OF BULLS BY ALLELIC VARIANTS OF THE CAPACASEIN GENE - Ладика, В. І.; Скляренко, Ю. І.; Павленко, Ю. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
An important issue in the selection of dairy cattle today is the study of the relationship between hereditary factors that determine the types of proteins in milk. Casein is the main component of milk proteins and is represented by three fractions - alpha (CSN1S1), beta (CSN2) and kappa (CSN3). The content of individual fractions of casein depends on the breed of cows. Genetic variants of kappa-casein are associated with the quality of milk productivity of cows and greater suitability for use of milk for processing and production of cheese. The kappa-casein B allele is associated with the production of milk, the chemical composition of which is more favorable and the technological parameters are more suitable for cheese production. The aim of the work is to assess the genotype of breeding bulls by the kappa-casein gene, which were approved for use in Ukrainian farms in 2020. It was found that most breeding bulls that are approved for use are evaluated by the genotype of kappa-casein. Breeding bulls of Swiss and Jersey breeds have a higher frequency of homozygotes of explosives (100 and 86.2%, respectively). The frequency of allele distribution in the kappa-casein gene in bulls of different breeds was higher in animals of Schwyz (1.00), Jersey (0.931) and Montbeliard breeds (0.813). Among breeding bulls of Holstein breed, no significant difference in milk yield, milk fat and protein between animals of all studied genotypes by kappa-casein and average by breed (among bulls of the catalog) was found. Breeding bulls with the BB genotype had a significant difference with bulls of other genotypes in all studied traits. Therefore, the use of sperm products of bulls approved for use in 2020, with the genotype of explosives for kappa-casein will improve the economically useful traits of offspring, and will contribute to the desired genotype of cows. When choosing bulls, cheese makers should pay attention not only to protein and somatic cell count (SCS). It is also important to have a high percentage of BB cows in the herd